Barriers in the Management of Tuberculosis in Rawalpindi, Pakistan: A Qualitative Study - Soomro, Munawar Hussain (National Research Institute of Tuberculosis and Lung Disease, 2013)
BACKGROUND: Tuberculosis (TB) is a contagious, airborne disease and remains a major global public health hazard. TB is a major cause of mortality and is affecting millions of people in low-income and middle-income countries. Worldwide, one person out of three is infected with the Mycobacterium tuberculosis. Timely diagnosis and treatment are the two key factors for better outcomes. Non-adherence to TB treatment is an important barrier for TB control programs. This study was designed to understand the barriers encountered by TB patients when seeking health care. MATERIALS AND METHODS: A qualitative study was conducted during the months of August and December 2010 on 15 health facilities. In-depth interviews were conducted with 23 TB patients (13 males and 10 females) aged 15-65 years. In addition, 15 health personnel were also interviewed. RESULTS: Most patients were found to be well informed about the idea of taking TB medications under direct supervision and its overall importance. However, many of them were not convinced with either drugs or treatment protocols. We found that limited knowledge of patients, loss of employment, financial burden, social stigma and long distance from health facility were the main barriers for TB adherence. CONCLUSION: More patient-centred interventions and attention to the barriers are required to improve the treatment adherence. Direct observation of patients and regular home visits by health workers can reduce the risk of non-adherence.